Laser induced breakdown spectroscopy methods and applications: A comprehensive review - Syed Kifayat, H. S.; Iqbal, Javed; Ahmad, P.; Khandaker, Mayeen Uddin *; Sirajul, H.; Naeem, Muhammad (Elsevier, 2020)
Laser induced breakdown spectroscopy has become an established analytical atomic emission spectroscopic technique. It has analytical and technical advantages over other existing techniques. It is a rapid, non-contact technique which is capable of providing qualitative and quantitative analytical information for any sample without any sample preparation. The instrumentation is simple, rebuts, compact and even provides remote analysis. The aim of the current study is to provide a critical review of “laser induced breakdown spectroscopy” in several aspects. First part focuses on the comparison of the “laser induced breakdown spectroscopy” with other well established techniques. In this section, the sensitivity, accuracy and sample preparation are compared and summarized. The second parts is a discussion on the experimental setup and instrumentation. In third part, a complete review of qualitative and quantitative analysis has been summarized. In addition, the effects of different experimental parameters and potential applications of “laser induced breakdown spectroscopy” in different fields of modern technologies have also been described in the current study.